Thermal retrofitting of worst performing buildings mitigates risk of high heating costs - Sophie M. Behr; Merve Kücük; Maximilian Longmuir; Karsten Neuhoff (DIW Weekly Report, 2024)
The pace of thermal retrofit of buildings in Germany remains slow. A Worst-First approach, prioritizing the retrofit of inefficient buildings, would address energy- and social policy objectives and deliver economic and climate benefits. Data from the German Socio-Economic Panel (SOEP) show how such an approach would protect especially low-income households often living in very inefficient buildings from heating costs risks. This group comprises 28 percent of all tenants and 13 percent of all homeowners. Yet, uncertainty about the cost-benefit of retrofitting and other priorities of homeowners mean that not enough buildings are retrofitted. As a result, the saving potentials, especially from very inefficient buildings, are not being realized. This would, however, be necessary to reduce heating cost risks and energy import dependency, and to meet climate targets. Better alignment of financing and subsidy instruments with the ownership structure, the further development of building standards to include minimum energy performance standards, and reform of tenancy law could improve the situation.
Keywords: D12; D31; L90; Q41; 330; retrofitting; heat energy; worst-first approach; minimum energy performance standards